Identification of 4-Chloromethylcathinone Metabolites in Urine with GC-MS and LC-QTOF - M.A. Gofenberg; V.A. Shevyrin (Emerging Trends in Drugs, Addictions, and Health)
Introduction: Synthetic cathinones are the most common group of new psychoactive substances found on the illegal Russian market. 1-(4-Chlorophenyl)-2-methylaminopropan-1-one (4-Chloromethylcathinone, Clephedrone, 4-CMC) is regularly found in urine samples from patients with acute stimulant poisoning and urine samples obtained from drivers suspected by police of driving under the influence of drugs. The aim of the study was to determine the metabolic profile of Clephedrone by GC-MS and LC-HRMS. Methods: Two urine samples from living individuals were used to search for Clephedrone metabolites and their glucuronides. 7890 gas chromatograph with HP-5MS column with 5977 mass spectrometer (Agilent Technologies) for determination of metabolites of I phase was used. Phase I and II metabolites were identified by liquid chromatography-high resolution mass spectrometry (LC-HRMS), which was performed on a 1290 Infinity II LC liquid chromatograph equipped with a Zorbax Eclipse Plus C18 column with a 6545 Q-TOF mass spectrometer (Agilent Technologies). Results: I and II phase metabolites of Clephedrone have been found in human urine. The main pathways of biotransformation include N-demethylation of the secondary amine to yield norclephedrone and reduction of the ketone moiety to the hydroxyl group to form dihydroclephedrone. Also identified is a metabolite obtained by loss of water by dihydroclephedrone to form a double bond. Minor pathways of biotransformation are associated with the oxidation of the methyl group of the propyl chain, hydroxylation at the benzene ring, and a combination of these reactions. Most of the metabolites were present in the urine, both in free and glucuronated forms. Conclusions: Synthetic cathinones are important psychostimulants that have been associated with driving disorders, intoxications, and fatal overdoses. The results of a study of the metabolism of 4-Chloromethylcathinone can be used to diagnose acute poisoning with synthetic cathinones, and to predict the directions of metabolism of new psychoactive substances.